Cover Picture: Reactivity and Operational Stability of N‐Tailed TAMLs through Kinetic Studies of the Catalyzed Oxidation of Orange II by H2O2: Synthesis and X‐ray Structure of an N‐Phenyl TAML (Chem. Eur. J. 16/2015). Issue 16 (13th April 2015) - Warner, Genoa R.; Mills, Matthew R.; Enslin, Clarissa; Pattanayak, Shantanu; Panda, Chakadola; Panda, Tamas Kumar; Gupta, Sayam Sen; Ryabov, Alexander D.; Collins, Terrence J.
<x xml:space="preserve">Abstract</x> "TAML activators" are full‐functional, small molecule peroxidase mimics that arguably outperform their enzyme progenitors (TAML=tetraamido macrocyclic ligand). In their Full Paper on page 6226 ff., S. S. Gupta, A. D. Ryabov, T. J. Collins et al. show that the Generation 5 (Gen‐5) TAML/H2O2 catalytic cycle follows the same path as Gen‐1 through Gen‐4. TAML reactivity in peroxide catalysis is subject to significant variation induced by small structural changes. The intergenerational comparative reactivity decreases in the series Gen‐4>Gen‐5>Gen‐1.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>